A systematic proactive risk assessment of hazards in surgical wards: a quantitative study. - Anderson, O; Brodie, A; Vincent, C; Hanna, G (2012)
OBJECTIVE: To identify and prioritize hazards in surgical wards and recommend interventions. BACKGROUND: Retrospective and prospective studies report the frequency and severity of surgical adverse events, but not in sufficient detail to allow interventions to be recommended in surgical wards. METHODS: Seventy hours of observations were used to record all activities occurring in surgical wards, and from these activities health care processes were derived. Fifty-nine patients and staff quantified the hazard associated with each health care process through a risk assessment survey. Modified health care failure mode and effects analysis was applied to the most hazardous of these processes to quantify the hazard of their associated failures. Cause analysis was applied to the most hazardous failures within analyzed processes. Interventions addressing the prioritized failures were recommended. RESULTS: Surgical ward observations identified 81 activities. The risk assessment survey was used to quantify the hazard associated with 10 health care processes derived from these activities. The 5 most hazardous processes were prioritized for modified health care failure mode and effects analysis including hand hygiene, isolation of infection, vital signs, medication delivery, and hand off. Of 190 failures within these processes, 50 (26%) were considered hazardous and did not have effective control measures in place. The causes of these failures allowed interventions to be recommended. CONCLUSIONS: Proactive risk assessments were used to systematically identify and prioritize hazards in surgical wards and allowed interventions to be recommended. These are practical tools that can determine where patient safety efforts should be targeted in clinical health care environments.